Three complementary approaches for crisis management. (27th June 2012) - Hernantes, Josune; Labaka, Leire; Laugé, Ana; Sarriegi, Jose María
Crisis is a wide concept which may include a diverse set of events and behaviour patterns. Thus, crisis management requires complementary approaches that provide a more complete perspective. This paper describes a useful methodology to analyse crises from a multiple perspective approach that contributes to acquire a more deep understanding about crises and their management. The first approach focuses on the peak of the crisis paying attention to how to respond to the crisis–triggering event and to the cascading effects that amplify the crisis impact. The second approach adopts a long–term perspective, identifying the relationship between the policies implemented on the pre–crisis phase and the subsequent impacts on the crisis peak and post–crisis phases. The third approach researches on the learning process from one crisis to the next one.